Державна політика зайнятості населення в епоху штучного інтелекту - Данильчук, Марія; Королюк, Тетяна (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
У статті розглядається вплив технологій штучного інтелекту на ринок праці у розрізі світових тенденцій та української перспективи. Описано виклики, які виникатимуть, та варіанти протидії. The article examines the impact of artificial intelligence technologies on the labor market in terms of global trends and the Ukrainian perspective. There are also described challenges that will arise and countermeasure options.